Evaluation of the Competitive Performance of the Largest Exporters In the Furniture Industry in the World - Katarzyna ŁUKIEWSKA (Communications of International Proceedings, 2022)
The aim of the study was to assess the competitive performance of the largest furniture exporters in the world in 2010, 2015 and 2020. Thus, not only the static aspect of competitiveness was taken into account, but also the dynamic. Indicators of export market share, trade coverage and revealed comparative advantages were calculated. Data from the UN COMTRADE database was used. The research shows that for years China has had the largest share in world furniture export. This country also showed by far the largest advantage in furniture trade and high comparative advantages. The high competitive performance of the furniture industry was also distinguished by Poland and Vietnam. Furthermore, an increasing importance of the Czech Republic and Turkey was observed, and a decreasing importance of Germany and Italy.
Keywords: competitiveness; competitive performance; world trade; furniture industry